Modern Approach to Conservative Treatment of Degenerative Diseases of Joints Using Regenerative Medicine Techniques - Martsynyak, Stepan M.; Chornobai, Serhii P.; Holyuk, Yevhen L.; Bondariev, Gennadii G. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(1): 079–083